Plasma CXCL14 as a Candidate Biomarker for the Diagnosis of Lung Cancer - Tian, Peng-Fei; Ma, Yu-Chen; Yue, Dong-Sheng; Liang, Fan; Li, Chen-Guang; Chen, Chen; Zhang, Hua; Sun, Xiao-Yan; Huang, Wu-Hao; Zhang, Zhen-Fa; Zhou, Guang-Biao; Wang, Gui-Zhen; et al. (Frontiers in Oncology, 2022)
Background Effective biomarkers for early diagnosis of lung cancer are needed. Previous studies have indicated positive associations between abnormal circulating cytokines and the etiology of lung cancer. Methods Blood samples were obtained from 286 patients with pretreatment lung cancer and 80 healthy volunteers. Circulating cytokine levels were detected with a Luminex assay and enzyme-linked immunosorbent assay (ELISA). Urine samples were obtained from 284 patients and 122 healthy volunteers. CXC chemokine ligand 14 (CXCL14) expression in tumors and nontumor regions of lung tissues from 133 lung cancer cases was detected by immunohistochemical (IHC) staining and immunofluorescence (IF) staining of formalin fixed paraffin-embedded (FFPE) tissues. Results Compared with healthy volunteers, a 65.7-fold increase was observed in the level of CXCL14 in the plasma of lung cancer patients, and a 1.7-fold increase was observed in the level of CXCL14 in the urine of lung cancer patients, achieving a 0.9464 AUC (area under the curve) value and a 0.6476 AUC value for differentiating between lung cancer patients and healthy volunteers, respectively. Stromal CXCL14 expression was significantly associated with advanced pathologic stage (P<0.001), pathologic N stage (P<0.001), and recurrence and metastasis (P=0.014). Moreover, multivariate analysis suggested stromal CXCL14 expression as an independent predictor of DFS and OS. Conclusions Our study demonstrates that CXCL14 might serve as a potential diagnostic and prognostic biomarker in patients with lung cancer. Impact CXCL14 might serve as a potential diagnostic and prognostic biomarker in patients with lung cancer.